Transformasi Paradigma Manajemen Strategi Dalam Konteks Volatilitas Global Dan Dinamika Kompetitif - syauqiyah, habibatus (Maliki Interdisciplinary Journal, 2024)
In an increasingly complex, unavoidable and dynamic business environment, the strategic management paradigm is undergoing a transformation that is very relevant. Global volatility, influenced by technological change, economic turmoil, and political and social dynamics, forces organizations to adapt quickly and effectively. Strategic management, once focused on stability and long-term planning, is now shifting to a more flexible and responsive approach. This article examines changes in the strategic management paradigm, identifies the key factors that influence them, and explores how organizations can develop more adaptive strategies in the face of global uncertainty and increasingly fierce business competition. Keywords: transformation; paradigm; strategic management; global volatility; competitive dynamics.